Using the Theory of Protected Needs to conceptualize sustainability as ‘caring for human wellbeing': an empirical confirmation of the theory's potential - Di Giulio, Antonietta; Defila, Rico; Ruesch Schweizer, Corinne (Frontiers in Sustainability, 2023)
Caring for human well-being has the potential of offering a powerful narrative for change towards sustainability. A broad body of research confirms that a narrative linking the ideas of a good life (human well-being) and of solidarity and justice actually exists, and that this narrative could, if supported and reinforced by convincing concepts, relevant material structures, and coherent action, serve as a societal source of power for sustainability. With a view to providing a theory of human well-being that focuses on the responsibility of the community and conceptualizes achieving a good life as a public good and not as a purely individual matter, we developed the Theory of Protected Needs (PN). The Theory of PN is a theory of good life that frames quality of life for individuals as a societal responsibility (but without affecting individual freedom), thus linking the individual and the societal perspective with a view of ensuring life satisfaction of present and future generations. The Theory of PN has been subjected to a representative survey in Switzerland. In the paper, we explore whether the Theory of PN can be empirically confirmed, that is, to what extent the nine needs the theory consists of deserve the status of being protected needs. We present the theory, the empirical criteria that the nine needs have to meet in order to qualify for being protected needs, and the results of the data analysis. These results sum up to an aggregated argument in favour of using the Theory of PN as a fundament to conceptualize sustainability as 'caring for human well-being'. The paper concludes with outlaying further steps both in research and in societal practice. In the Appendix, the German and French versions of the Theory of PN are first published.